Projecting cardiovascular deaths averted due to trans fat policies in the Eurasian Economic Union - Matthias Rieger; Holly L Rippin; Adriana Pinedo; Stephen Whiting; Clare Farrand; Kremlin Wickramasinghe; Joao J Breda (Public Health Nutrition, 2023)
Abstract